PENGARUH PROFITABILITAS DAN RASIO AKTIVITAS TERHADAP PERTUMBUHAN LABA PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Handayani, Sri Fatma; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to test partially and simultaneously the effect of profitability and activity ratios on the company's profit growth. Where the independent variable in this study is profitability and activity ratio while the dependent variable is profit growth. The sample used is secondary data derived from the financial statements of mining companies listed on the Indonesia Stock Exchange (IDX) in 2014 to 2017. This study uses secondary data from the company's financial statements. Sampling uses census techniques. Data analysis using multiple linear regression analysis, t test, F test, and test coefficient of determination. Data analysis using multiple linear regression analysis with SPSS 23. The results of this study indicate that the profitability variable partially (t test) has a positive and significant effect on earnings growth, while the activity ratio variable has a negative and not significant effect on profit growth in mining companies listed on the Indonesia Stock Exchange. The simultaneous test results (F) show the influence of profitability variables and the ratio of activity to profit growth in mining companies listed on the Indonesia Stock Exchange.Â Keywords: Profitability, Activity Ratio, and Profit Growth